IMPLEMENTASI PEMBELAJARAN KOOPERATIF MODEL THINK PAIR SHARE DAN LEARNING TOGETHER DENGAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK DITINJAU DARI MINAT BELAJAR SISWA - Mardodo Mardodo; Budiyono Budiyono; Imam Sujadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objective of research was to find out: (1) which ones having better achievement, the students using TPS (Think Pair Share) learning model with RMA, LT (Learning Together) learning model with RMA or Direct Instruction, (2) Viewed from students’ interest, high, middle, and low, which ones having better achievement, the students using TPS (Think Pair Share) learning model with RMA or LT (Learning Together) learning model with RMA or Direct Instruction, and (3) students’ achievement  viewed from students’ interest on each learning model. The type of the research was a quasi-experimental research.  The population of research was all VIII graders of  Public Junior High schools in Karanganyar Regency consisting of 75 schools. The sample was taken using cluster random sampling. The size of the sample was 261 students consisted of  87 students in the first experimental group, 87 students in the second experimental group and 87 students in the control group. Collecting data has been done through multiple choice test to know students’ achievement and questionnaire to know students interest in learning. Data analysis technique used two-way analysis of variance with unbalanced cells. The conclusions of research as follows: (1) TPS with RMA provided learning achievement better than LT with RMA and Direct Instruction, and LT with RMA provided learning achievement better than the Direct Instruction. (2) Viewed from students’ interest, in   the high interest, TPS with RMA provided learning achievement as LT with RMA did, also LT with RMA provided learning achievement as Direct Instruction did, but TPS with  RMA provided learning achievement better than Direct Instruction did. In the midlle and low interest, all learning models provided the same learning achievement. (3) In TPS with RMA, the students with high interest had better achievement than those with middle and low interest. Meanwhile, in both LT with RMA and In Direct Instruction, the students with three categories of interest had the same learning achievement.Keywords: TPS with Realistic Mathematics Approach (RMA), LT with RMA, Interest Learning, Students Achievement on mathematics.